HER2 exon 20 insertions in non-small-cell lung cancer are sensitive to the irreversible pan-HER receptor tyrosine kinase inhibitor pyrotinib. (31st December 2018) - Wang, Y; Jiang, T; Qin, Z; Jiang, J; Wang, Q; Yang, S; Rivard, C; Gao, G; Ng, T L; Tu, M M; Yu, H; Ji, H; et al.
Abstract: Background: Effective targeted therapy for non-small-cell lung cancer (NSCLC) patients with human epidermal growth factor receptor 2 ( HER2 ) mutations remains an unmet need. This study investigated the antitumor effect of an irreversible pan-HER receptor tyrosine kinase inhibitor, pyrotinib. Patients and methods: Using patient-derived organoids and xenografts established from an HER2-A775_G776YVMA-inserted advanced lung adenocarcinoma patient sample, we investigated the antitumor activity of pyrotinib. Preliminary safety and efficacy of pyrotinib in 15 HER2-mutant NSCLC patients in a phase II clinical trial are also presented. Results: Pyrotinib showed significant growth inhibition of organoids relative to afatinib in vitro ( P = 0.0038). In the PDX model, pyrotinib showed a superior antitumor effect than afatinib ( P = 0.0471) and T-DM1 ( P = 0.0138). Mice treated with pyrotinib displayed significant tumor burden reduction (mean tumor volume, −52.2%). In contrast, afatinib (25.4%) and T-DM1 (10.9%) showed no obvious reduction. Moreover, pyrotinib showed a robust ability to inhibit pHER2, pERK and pAkt. In the phase II cohort of 15 patients with HER2 - mutant NSCLC, pyrotinib 400 mg resulted in a objective response rate of 53.3% and a median progression-free survival of 6.4 months. Conclusion: Pyrotinib showed activity against NSCLC with HER2 exon 20 mutations in both patient-derived organoids and a PDX model. In the clinical trial, pyrotinib showed promising efficacy. Clinical trial registration: NCT02535507.